2012
DOI: 10.1136/archdischild-2011-300626
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in children with type 1 diabetes in the first year after diagnosis: relationship to glycaemic control and cardiovascular risk

Abstract: Insulin deficiency at diagnosis of diabetes causes a catabolic state that is predominantly lipolytic. Body composition normalises within 6 weeks of treatment, though girls remain thinner than boys both at diagnosis and 1 year thereafter, in contrast to published findings. Despite girls being prescribed a larger insulin dose, their HbA1c and cholesterol levels are higher at 1 year suggesting increased insulin resistance and cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
3
35
2
Order By: Relevance
“…Because the baseline visit occurred on average ~10 months after they were diagnosed with type 1 diabetes, these results could indicate that weight status within the first 6 months of diabetes diagnosis is an important predictor of longitudinal adiposity. This finding conflicts with data from a small clinical study which showed that girls with type 1 diabetes were leaner at diagnosis and 1 year following diagnosis as compared to males, suggesting that obesity in females may onset later in the disease course …”
Section: Discussioncontrasting
confidence: 89%
“…Because the baseline visit occurred on average ~10 months after they were diagnosed with type 1 diabetes, these results could indicate that weight status within the first 6 months of diabetes diagnosis is an important predictor of longitudinal adiposity. This finding conflicts with data from a small clinical study which showed that girls with type 1 diabetes were leaner at diagnosis and 1 year following diagnosis as compared to males, suggesting that obesity in females may onset later in the disease course …”
Section: Discussioncontrasting
confidence: 89%
“…In contrast with the results reported by other studies, only five participants (adolescents) in this study were overweight, and none of the participants were obese; however, the percent of body fat was higher for all females than recommended for their age (31.2% body fat). This has also been reported for Swedish adolescent females with T1DM (22) and adolescents females in the United Kingdom (23) . The Brought to you by | Bibliotheque de l'Universite Laval Authenticated Download Date | 7/1/15 9:36 PM Data are presented as mean ± standard deviation.…”
Section: Discussionmentioning
confidence: 56%
“…It is vital that energy intake is reduced when appropriate weight is restored . The first year following diabetes onset is a critical period to ensure excessive weight is not gained and to promote maintenance of a healthy body weight Energy intake varies greatly within subjects on a daily basis due to age, growth rate, physical activity and important environmental factors such as the type and availability of food. Energy intake should be sufficient to achieve optimal growth and maintain an ideal body weight. Flexibility in the advice about the amount of food to meet varying energy needs is necessary.…”
Section: Introductionmentioning
confidence: 99%